2014
DOI: 10.1007/s00381-014-2442-3
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous malformations of the central nervous system (CNS) in children: clinico-radiological features and management outcomes of 36 cases

Abstract: Younger children tend to harbor larger CMs and present with hemorrhage more frequently than older ones. Microsurgical resection should be the treatment of choice in symptomatic and accessible CMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 36 publications
1
17
1
Order By: Relevance
“…6 Cavernous malformations comprise about 20% of all intracranial and intraspinal vascular malformations, and one-fourth of them are reported under 18 years of age. 8,9 The mean age at symptom onset in our series was 9.3 years, which was similar to the literature. 5,10 It has been reported that there exists a bimodal age distribution in pediatric cavernous malformations: in the age group of 0-3 and 11-16 years.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…6 Cavernous malformations comprise about 20% of all intracranial and intraspinal vascular malformations, and one-fourth of them are reported under 18 years of age. 8,9 The mean age at symptom onset in our series was 9.3 years, which was similar to the literature. 5,10 It has been reported that there exists a bimodal age distribution in pediatric cavernous malformations: in the age group of 0-3 and 11-16 years.…”
Section: Discussionsupporting
confidence: 89%
“…Second, it is reported that cavernous malformation patients with a prior hemorrhage history have a significantly increased risk of bleeding at the rate of 4.5% to 22.6% per year. 9 Third, pediatric patients have a longer life expectancy, which results in a higher accumulative risk than adult counterparts. Fourth, frontal lobe cavernous malformations locate at accessible sites, and the surgical risk is relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…Resection is generally recommended for symptomatic easily accessible CCMs given the increased risk of rebleed after first hemorrhage, and the low morbidity associated with surgery. 87 , 88 Other considerations are needed for CCMs involving the visual pathways, 89 , 90 and those involving the lateral ventricle. 91 …”
Section: Neurosurgical Considerationsmentioning
confidence: 99%
“…Because of the benign biological behavior and clear lesion boundaries with the surrounding brain tissue, it is suitable for surgical resection [1,10]. However, for cavernous hemangioma deep within the hemisphere, especially lesions involving important structures, surgery is also controversial [7].…”
Section: Discussionmentioning
confidence: 99%